2022
DOI: 10.1111/jocn.16467
|View full text |Cite
|
Sign up to set email alerts
|

The impact of COVID‐19 on nurse alcohol consumption: A qualitative exploration

Abstract: Aims and objectives To explore the long‐term impact of the COVID‐19 pandemic on nurse alcohol consumption. Background The COVID‐19 pandemic has caused immense disruption to healthcare services worldwide, and nurses have not been immune, experiencing burnout, declining mental health and ultimately, attrition from the profession. Increases in alcohol consumption have been reported across subsections of society, including those with pre‐existing mental ill health and exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…In line with COVID-19-related research from around the world (e.g., Australia, the US, France, Denmark and Norway), increases in alcohol consumption were linked to loneliness, boredom and stress while decreases were linked mainly to a lack of socialising during periods of lockdown (Biddle, 2020;Birkeland Nielsen et al, 2021;Flaudias et al, 2020;Hagen et al, 2022;Hviid et al, 2023;Rodriguez et al, 2020;Searby et al, 2022).…”
Section: Discussionmentioning
confidence: 56%
“…In line with COVID-19-related research from around the world (e.g., Australia, the US, France, Denmark and Norway), increases in alcohol consumption were linked to loneliness, boredom and stress while decreases were linked mainly to a lack of socialising during periods of lockdown (Biddle, 2020;Birkeland Nielsen et al, 2021;Flaudias et al, 2020;Hagen et al, 2022;Hviid et al, 2023;Rodriguez et al, 2020;Searby et al, 2022).…”
Section: Discussionmentioning
confidence: 56%
“…A qualitative study of 42 Australian nurses concluded that several participants disclosed their increased alcohol consumption during COVID-19, particularly due to the stressful work environment. Workplace factors such as overtime, scarce resources, missed breaks and heightened workload, were all described as driving stressors for alcohol consumption (35). Remarkably, a Californian thesis explored the incidence of substance use among nurses prior to the pandemic versus today and said that alcohol was the most prevailing substance used by nurses during the pandemic, followed by tobacco and marijuana (36).…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, healthcare personnel are responsible for providing collaborative services to the population of all ages, with the aim of achieving optimal overall functioning of the health system 6 . It has been documented that working in an environment with inadequate breaks, working more than eight hours, rotation of schedules and scarcity of resources can negatively affect the health of the healthcare personnel 7,8 . Although stress, lack of education and lack of knowledge about alcohol abuse are some factors that may influence the ingestion of this substance 9 .…”
Section: Introductionmentioning
confidence: 99%